2020
DOI: 10.3390/jcm9020331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations, Pathogenesis and Treatment of Hepatitis E Virus Infections

Abstract: Hepatitis E virus (HEV) is the most common cause of acute viral hepatitis throughout the world. Most infections are acute but they can become chronic in immunocompromised patients, such as solid organ transplant patients, patients with hematologic malignancy undergoing chemotherapy and those with a human immunodeficiency virus (HIV) infection. Extra-hepatic manifestations, especially neurological and renal diseases, have also been described. To date, four main genotypes of HEV (HEV1-4) were described. HEV1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 209 publications
0
97
0
3
Order By: Relevance
“…Overall, GT3 is responsible for the majority of the autochthonous cases in Europe [ 14 ]. Seroprevalence in European countries ranges from 5% [ 15 , 16 ] to 50% in some regions of Southern France [ 17 ]. Differences in seroprevalence may be a consequence of the sensitivity of the anti-HEV antibody detection assay employed [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, GT3 is responsible for the majority of the autochthonous cases in Europe [ 14 ]. Seroprevalence in European countries ranges from 5% [ 15 , 16 ] to 50% in some regions of Southern France [ 17 ]. Differences in seroprevalence may be a consequence of the sensitivity of the anti-HEV antibody detection assay employed [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In immunocompromised individuals who receive immunosuppressive therapy following solid organ transplantation or stem cell transplantation [75][76][77] and those with human immunodeficiency virus (HIV) infection [78,79] or with hematological malignancy [80][81][82], chronic HEV infection may develop. This disease course of chronic infection has mainly been reported for HEV-3 and 4, leading to life-threatening liver fibrosis and cirrhosis [75,80,[83][84][85]. It has been reported that HEV-3 can cause acute hepatitis E in pregnant women, followed by rapid clearance without any signs of severe courses [50,51].…”
Section: Chronic Hepatitis Ementioning
confidence: 96%
“…Acute or chronic or previous HEV infection can cause extrahepatic manifestations [86,87], which include a range of neurological symptoms and impaired kidney function associated with cryoglobulinemia [84,88]. Other extrahepatic manifestations documented in the literature include acute thyroiditis [89], thrombocytopenia [90], and acute pancreatitis [91].…”
Section: Extrahepatic Manifestations Of Hepatitis Ementioning
confidence: 99%
“…In general, acute HEV infection is relatively asymptomatic or mildly symptomatic. However, acute icteric hepatitis is seen in almost 5%-30% of patients infected by the HEV[ 62 ]. Malaise, fever, body aches, nausea, and vomiting are characteristic symptoms observed through the 1-wk prodromal phase of acute icteric hepatitis, which is followed by the icteric phase lasting approximately 1 wk.…”
Section: Clinical Manifestations Of Hev Infectionsmentioning
confidence: 99%
“…Malaise, fever, body aches, nausea, and vomiting are characteristic symptoms observed through the 1-wk prodromal phase of acute icteric hepatitis, which is followed by the icteric phase lasting approximately 1 wk. It is marked by dark-colored urine and jaundice[ 62 ]. Then, the convalescent phase results in the resolution of icteric symptoms.…”
Section: Clinical Manifestations Of Hev Infectionsmentioning
confidence: 99%